ERADICATION OF HETEROGENEOUS VANCOMYCIN ITERMEDIATED STAPHYLOCOCCUS AUREUS (hVISA) USING PEGANUM HARMALA L. SEEDS EXTRACTS - Osamah Z. Al-Hayali,; M. F. Al Marjani,; A. Maleki, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The main purpose of this research is to evaluate the antibacterial essential oil of Peganum harmala L. seeds against locally isolated heterogeneous vancomycin intermediated Staphylococcus aureus (hVISA) at doses ranging from 0.03 to 200 mg/ml. The filtered essential oil of P. harmala, after extract by the 96% ethanol in a Soxhlet extraction device, was analyzed by GC/MS (gas chromatography-mass spectroscopy). The results showed that the P. harmala seeds oils contained several compounds, such as Harmine (58.26%), followed by 9,12-Octadecadienoic acid (Z,Z)-, methyl ester (28.55%) and Hexadecanoic acid, methyl ester (4.30%), It is highly effective against targeted bacteria. The MIC method was used to investigate antibacterial activity by measuring the lowest inhibitory concentration of the extract and observed that the inhibition concentration against hVISA isolates was 0.3 mg/ml. The gene expression was detected after RNA extract from hVISA (untreated and treated) with P. harmala essential oil using the Quantitative Real-Time PCR method the results revealed that gene expression was low after bacterial with plant extract treatment. Finally, the ethanolic extract of p. harmala seeds appears to be a potential therapy choice for hVISA infection.